Epitranscriptomic RNA Methylation in Plant Development and Abiotic Stress Responses - Hu, Jianzhong; Manduzio, Stefano; Kang, Hunseung (Frontiers in plant science, 2019)
Recent advances in methylated RNA immunoprecipitation followed by sequencing and mass spectrometry have revealed widespread chemical modifications on mRNAs. Methylation of RNA bases such as -methyladenosine (m A) and 5-methylcytidine (m C) is the most prevalent mRNA modifications found in eukaryotes. In recent years, cellular factors introducing, interpreting, and deleting specific methylation marks on mRNAs, designated as "writers (methyltransferase)," "readers (RNA-binding protein)," and "erasers (demethylase)," respectively, have been identified in plants and animals. An emerging body of evidence shows that methylation on mRNAs affects diverse aspects of RNA metabolism, including stability, splicing, nucleus-to-cytoplasm export, alternative polyadenylation, and translation. Although our understanding for roles of writers, readers, and erasers in plants is far behind that for their animal counterparts, accumulating reports clearly demonstrate that these factors are essential for plant growth and abiotic stress responses. This review emphasizes the crucial roles of epitranscriptomic modifications of RNAs in new layer of gene expression regulation during the growth and response of plants to abiotic stresses.